PENANAMAN NILAI KARAKTER MELALUI HIZBUL WATHAN - Tong, Jailani; Asep Supena; Eko Siswono (Jurnal Pendidikan Dasar, 2021)
The research aims to describe the process and strategy of character value inculcation in elementary schools. The study was conducted using a qualitative case-study method, at one of Muhammadiyah's elementary schools in Jakarta. Subjects in the study were the principal, deputy headmaster for student affairs, coach Hizbul Wathan. Data was collected through in-depth interviews, observation, and document study. Stages and procedures of data analysis are done through data reduction, data display and conclusion drawing. The results showed that (1) Character values ​​developed in schools are religious, disciplined, responsible and caring for the environment, (2) There are four main methods used to strengthen student character, namely motivating, advising, appreciating and exemplary, (3) There are a number of supporting and inhibiting factors for character building activities that originate from schools, students and parents